2017
DOI: 10.1002/lary.26831
|View full text |Cite
|
Sign up to set email alerts
|

Partial inferior turbinectomy in rhinoseptoplasty has no effect in quality‐of‐life outcomes: A randomized clinical trial

Abstract: Objective: Evaluate the impact of endoscopic partial inferior turbinectomy (EPIT) associated with primary rhinoseptoplasty on quality-of-life outcomes (QOL), complications, and surgical duration.Study Design: Randomized clinical trial. Methods: Individuals with nasal obstruction aged 16 years who were candidates for functional and aesthetics primary rhinoseptoplasty were evaluated from March 2014 through May 2015. Eligible participants were randomly allocated to rhinoseptoplasty with or without EPIT (excision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 40 publications
5
21
1
Order By: Relevance
“…Our results are in agreement with those of a recent, randomized, controlled study with a design similar to ours. Although that study evaluated non‐AR patients, the authors concluded that septoplasty alone may be adequate, similar to our finding for AR patients …”
Section: Discussionsupporting
confidence: 86%
“…Our results are in agreement with those of a recent, randomized, controlled study with a design similar to ours. Although that study evaluated non‐AR patients, the authors concluded that septoplasty alone may be adequate, similar to our finding for AR patients …”
Section: Discussionsupporting
confidence: 86%
“…[4][5][6] Rhinoseptoplasty is also often performed concomitantly with inferior turbinate surgery with the aim of preserving the total breathing area which is surgically reduced, even though there is no evidence of efficacy regarding this aspect. [7][8][9][10][11][12] Allergic rhinitis (AR) is one of the main causes of turbinate enlargement. 13 It is characterized by hypersensitivity induced by immune-mediated inflammation resulting from the exposure of the nasal mucosa to specific allergens.…”
Section: Introductionmentioning
confidence: 99%
“…Further observed was that partial turbinectomy did not cause any significant complications [17]. In a study conducted by de Moura et al [18], it was concluded that sub mucosal partial inferior turbinectomy is a reliable surgical technique that does not entail any serious complications; this method, however, is not effective in improving the quality of life in short-term periods following the surgery. In the present research, no significant difference was observed concerning the SNOT-22 questionnaire up to 1 month after the surgery.…”
Section: Discussionmentioning
confidence: 99%